The determinants of household debt in 5 selected ASEAN countries / Nur Amalin Mohammad Nasir - Mohammad Nasir, Nur Amalin (PCP Publications, 2019)
The level of Asean's household debt can lead to another financial crisis, as it is at worrying stage. Therefore, the aims of this study is to identity the relationship between household debt and its determinants as well as to determine the most significant factor that affect the household debt by using panel data. It influenced by the variables which include gross domestic product, inflation rate, house price index, interest rate and unemployment rate. Fixed Effect Regression Model has been selected in this study with the data collected from 2007 until 2017 in quarterly basis based on Bloomberg database, Eikon Thomson Reuters, Fred Economic Data, Department of Statistics Malaysia, CEIC Data and Trading Economics. As an additional analysis, it revealed that there is significant relationship for house price index, unemployment rate and inflation rate with household debt. A part from that the result also revealed there is insignificant relationship for gross domestic product and interest rate with household debt. In conclusion, these findings bear important implications for every country's policymakers.